1991
DOI: 10.1038/jcbfm.1991.129
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Kinetics of 3-O-Methyl-6-[18F]fluoro-L-DOPA in the Rhesus Monkey Brain

Abstract: Summary: Most attempts to model accurately [18FI_ DOPA imaging of the dopamine system are based on the assumptions that its main peripheral metabolite, 3-crosses the blood-brain barrier but is present as a homog enous distribution throughout the brain, in part because it is not converted into e8F]DOPA in significant quantities, These assumptions were based mainly on data in rodents. Little information is available in the primate. To verify the accuracy of the above assumptions, we administered 1 8F-labeled 3-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Doudet et al (1991) reported a COY of 10% for the striatal Ve of OMFD in four monkeys. Koeppe et al (1990) The partition volume also underlies the essential difference between the kP and kj analyses.…”
Section: Md(t) + Mm(t) R(t) = M�(t) + M�(t)mentioning
confidence: 98%
“…Doudet et al (1991) reported a COY of 10% for the striatal Ve of OMFD in four monkeys. Koeppe et al (1990) The partition volume also underlies the essential difference between the kP and kj analyses.…”
Section: Md(t) + Mm(t) R(t) = M�(t) + M�(t)mentioning
confidence: 98%
“…The partition volume is equal to the distribution volume of those tracers at steady-state. Doudet et al (1991) demon strated that the partition volume of OMFD is the same in practically all brain regions, including the striatum. Because Koeppe et al (1990) reported a small intrasubject variability of the partition volume (with a frontal-to-occipital gradient) of [IlC]ami nocyclohexanecarboxylate, we chose the V e value of the frontal cortex for the striatum.…”
Section: Biological Constraintsmentioning
confidence: 99%
“…While FDOPA is well validated as a dopaminergic tracer (Eidelberg et al, 1994; Pate et al, 1993; Vingerhoets et al, 1994), it has the disadvantage of being subject to peripheral metabolism by catechol-O-methyltransferase (COMT). The resulting methylated metabolites are transported across the blood-brain barrier by the large neutral amino acid transporter and contribute to the PET signal in the brain thereby degrading the signal to noise ratio and complicating kinetic modeling (Doudet et al, 1991; Wahl et al, 1994). An alternative AADC tracer, 6-[ 18 F]fluoro-L-m-tyrosine (FMT), is not subject to O-methylation resulting in better quality images with higher signal to noise and more straightforward kinetics (DeJesus et al, 1997; Jordan et al, 1997; Nahmias et al, 1995).…”
Section: Introductionmentioning
confidence: 99%